The healthy eating pyramid - Video Education Australasia (Bendigo, Vic. : Video Education Australasia, 2001)
Covers the Healthy Eating Pyramid and the Healthy Eating Pyramid for Lacto-ovo Vegetarians. Emphasises the need to reduce the intake of saturated fat, salt and refined foods and to increase the intake of complex carbohydrates. Stresses the need for regular activity or sport to be part of everyone's healthy lifestyle
DVD format
Keywords: Diet; Nutrition